Clinical presentation, diagnosis, and treatment of caudal mediastinal paraesophageal abscesses in dogs: a multi-institutional retrospective study - Kathryn Biehl; Rachel W. Williams; Emily Orr; Kelley Thieman Mankin; Hunter Piegols; Jordyn Blew; David E. Holt; Francesca P. Solari; Federico R. Vilaplana Grosso (American Journal of Veterinary Research, 2026)
Abstract Objective To describe the clinical presentation, diagnostic findings, management, and short- and long-term outcomes of dogs with caudal mediastinal paraesophageal abscesses (CMPA) in a multi-institutional retrospective cohort. Animals 12 client-owned dogs with CMPA confirmed on CT and/or surgery. Clinical Presentation The most common presenting complaints were inappetence and lethargy. Tachypnea and dyspnea were frequent physical examination findings at presentation. Results All 12 dogs underwent CT. The CMPA was located within the mediastinal serous cavity in 7 of 12 dogs. Communication between the CMPA and the lumen of the esophagus was noted in 3 dogs, all of which had associated esophageal foreign bodies. Ten dogs underwent surgical treatment, which involved drainage (n = 8) and debridement (7) of the abscess, combined with antimicrobial therapy. All dogs who survived surgery were discharged from the hospital. No recurrence was identified in dogs with available long-term follow-up. Clinical Relevance In dogs, CMPA is associated with nonspecific clinical signs, and CT is the imaging modality of choice for diagnosis. Treatment, including surgical drainage, debridement, and appropriate antimicrobial therapy, is associated with a favorable prognosis.